Three-Component One-Pot Reactions of 2-Trifluoromethyl-N-nosylaziridine, Primary Amines, and Vinylsulfonium Salts for Convenient Access to CF3-Containing Piperazines - Hirotaki, Kensuke; Irie, Akiko; Nakamura, Yuki; Hanamoto, Takeshi (Synthesis, 2017)
Trifluoromethylated piperazines were readily synthesized with excellent regioselectivity in high yields by the sequential reaction of 2-trifluoromethylated N-nosylaziridine (2-CF3-N-Ns-aziridine) with various primary amines, followed by treatment with vinylsulfonium salts, in one pot.
Keywords: fluorine; aziridine; vinylsulfonium salt; cyclization; piperazine; regioselectivity